Social Solidarity of the Naqsyabandiyah Congregation - Yessy Afdani (BELIEF: Sociology of Religion Journal, 2023)
This study examines the solidarity of the congregation in interpreting togetherness in suluk or tarekat activities, secondly, what forms of solidarity exist in implementing the teachings of the Naqsyabandiyah Tarekat, the aim is first, to find out the solidarity of the congregation in interpreting togetherness in suluk or tarekat activities, secondly to find out solidarity in implementing the teachings Naqshbandiyah order. This research uses a field approach by means of observation, interviews and documentation. Using qualitative methods with a descriptive study design by conducting interviews as a technique for collecting data, interpreting data, and visualizing data. The results of this research show that the place of the Naqsyabandiyah congregation is in Lasi Mudo, which is brought by three great scholars, namely, Sheikh Damanhuri, Sheikh Muhammad Zen and Sheikh H. Jamaah Ahmad. Suluk is carried out in the month of Ramadan and in bersuluk there is also togetherness, namely when breaking the fast, sahur with congregational prayers and when performing tawajjuh in bersuluk. The congregation also performs prayers every time, and will also perform tawajjuh together with other congregations led by the murshid. In bersuluk there are also rules for eating, not eating blood or flesh, not eating a lot, and sleeping for a long time. While performing the bersuluk, you are not allowed to talk much to other congregants except your murshid. In suluk activities, there is little social solidarity. Because of this Suluk we focus on facing Allah.